2012
DOI: 10.1016/j.neuropharm.2012.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor regulates adult hippocampal cell proliferation through MEK/ERK- and PI3K/Akt-dependent signaling

Abstract: Vascular endothelial growth factor (VEGF) is a hypoxia-induced angiogenic protein that exhibits a broad range of neurotrophic and neuroprotective effects in the central nervous system. Given that neurogenesis occurs in close proximity to blood vessels, increasing evidence has suggested that VEGF may constitute an important link between neurogenesis and angiogenesis. Although it is known that VEGF can directly stimulate the proliferation of neuronal progenitors, the underlying signaling pathways responsible in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 85 publications
7
118
0
1
Order By: Relevance
“…VEGF can also increase phospho-ERK and stimulate the ERK1/2 signaling pathway (43,44). A recent study reported that a single treatment of VEGF activated ERK1/2 and AKT signaling pathways in the adult rat hippocampus and in cultured hippocampal neuronal progenitor cells (45). Consistent with these observations, our results showed that VEGF could phosphorylate ERK1/2 to activate it in HA-VSMCs (Fig.…”
Section: Stat3 and Myocardin Can Regulate The Expression Ofsupporting
confidence: 91%
See 1 more Smart Citation
“…VEGF can also increase phospho-ERK and stimulate the ERK1/2 signaling pathway (43,44). A recent study reported that a single treatment of VEGF activated ERK1/2 and AKT signaling pathways in the adult rat hippocampus and in cultured hippocampal neuronal progenitor cells (45). Consistent with these observations, our results showed that VEGF could phosphorylate ERK1/2 to activate it in HA-VSMCs (Fig.…”
Section: Stat3 and Myocardin Can Regulate The Expression Ofsupporting
confidence: 91%
“…In addition, ERK1/2 signaling is activated via VEGF and plays a role in cell death by oxygen glucose deprivation (44). A single treatment of VEGF activated ERK1/2 and AKT signaling pathways in the adult rat hippocampus and in cultured hippocampal neuronal progenitor cells (45). VEGF increases phospho-ERK and phospho-AKT in phrenic motor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blood circulating factors have substantial effects over the process of neurogenesis (79)(80)(81)(82). VEGF is one of these factors (83), and can stimulate neurogenesis (84)(85)(86) and reversibly modulate neuronal plasticity (87). Other blood-derived factors capable of affecting neurogenesis are glucocorticoids, which are necessary for the regulation of neuronal differentiation and migration (88).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt pathway has been implicated in VEGF signaling (13,14). To identify potential mechanisms for VEGF-B activity on peripheral nerves, we used a specific PI3K inhibitor and demonstrated that the PI3K pathway is required for VEGFinduced neurite elongation (Fig.…”
Section: Significancementioning
confidence: 99%